Knowledge Mapping in Agricultural Economics - Fahrati, Eny; Sopiana, Yunita (West Science Nature and Technology, 2024)
This study utilizes VOSviewer to conduct a bibliometric analysis of the agricultural economics literature, identifying thematic clusters, research trends, research opportunities, and collaboration networks among authors. Thematic cluster analysis reveals distinct research domains such as macroeconomic impacts, technology in agriculture, productivity, and efficiency. Research trend analysis over time shows a shift from foundational studies towards more integrated approaches focusing on the impact of technological advancements and policy changes on agricultural productivity and efficiency, especially from the mid-1990s to the 2010s. Further, the exploration of less illuminated areas within the network maps highlights underexplored topics such as agricultural markets, labor, and exports, presenting new opportunities for future research. Author collaboration networks reveal both dense clusters of frequent collaborators and key individuals linking various research areas, reflecting the collaborative nature of the field. These findings underscore the evolving dynamics of agricultural economics research and provide a roadmap for addressing both micro and macro-level challenges within the sector.